Temporary Employment Contract Elements - Dr. Mohammed Jawad Bahraini; Lazem Sultan Abdul Husseinawi (International Journal of Medical Toxicology and Legal Medicine, 2024)
A temporary employment contract is one of the forms of employment that responds to the needs of the modern labor market, as it depends on providing labor for a specific period of time based on a prior agreement between the worker and the employer. This type of contract is highly flexible, allowing business owners to meet their changing labor needs without committing to long-term employment relationships temporary employment contract represents a worker with an opportunity to obtain employment at certain times, but it also reflects a degree of instability and a lack of long-term guarantees provided by a permanent employment contract.